La inducción analítica como método sociológico desde una perspectiva histórica - Sosa, Andrea Patricia (2019)
The aim of this article is to study analytic induction as a scientific research method, that is, as a valid way of making science. In 1934, the philosopher and sociologist Florian Znaniecki, its creator, referred to this methodology as the method that should be adopted by any sociological research. Its relevance lies on the fact that its goal is to find global explanations to social phenomena by using qualitative research techniques. I adopt a historical perspective to inscribe this method's emergency and evolution in a larger context of the development of qualitative methods in sociology, and then reflect upon its epistemological basis and the criticisms made in relation to it. Finally, I evaluate this method's contributions to the discipline.